Efisiensi Adsorpsi Beberapa Zat Warna Sintetis Golongan Azo Menggunakan Hidroksiapatit - Siti Rahmalia; Yelmida Azis; Ida Zahrina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The removal efficiency of adsorption is very dependent on the type of adsorbent. The use of hydroxyapatite as an adsorbent for synthetic dyes still needs to be developed. The aim of this study was to determine the effects of dyes and adsorbent mass on removal efficiency, and the best conditions in the adsorption process using of hydroxyapatite. Analysis was conducted by spectrophotometric and Fourier Transform Infrared (FTIR) methods. The results showed that the mass of the adsorbent affects the removal efficiency of dyes. The best removal efficiency is at 0.5 g adsorbent mass for each dye. Adsorption capacity for methylene blue at 2 minutes was 1.96 mg/g with 26,12% of removal efficiency. Adsorption capacity for methyl red at 5 minutes was 6.68 mg/g with 89% of removal efficiency. Dye adsorption was not found during adsorption process of methyl orange. Fourier Transform Infrared (FTIR) analysis showed that there was no adsorption of azo group on all spectra, indicated that there was not chemical reaction between the adsorbent and the adsorbate during the adsorption process.Key Words: adsorption, hydroxyapatite, methyl orange, methyl red, methylene blue.